Nuclear transport genes recurrently duplicate by means of RNA intermediates in Drosophila but not in other insects - Ayda Mirsalehi (BMC, 2021)
Abstract Background The nuclear transport machinery is involved in a well-known male meiotic drive system in Drosophila. Fast gene evolution and gene duplications have been major underlying mechanisms in the evolution of meiotic drive systems, and this might include some nuclear transport genes in Drosophila. So, using a comprehensive, detailed phylogenomic study, we examined 51 insect genomes for the duplication of the same nuclear transport genes. Results We find that most of the nuclear transport duplications in Drosophila are of a few classes of nuclear transport genes, RNA mediated and fast evolving. We also retrieve many pseudogenes for the Ran gene. Some of the duplicates are relatively young and likely contributing to the turnover expected for genes under strong but changing selective pressures. These duplications are potentially revealing what features of nuclear transport are under selection. Unlike in flies, we find only a few duplications when we study the Drosophila duplicated nuclear transport genes in dipteran species outside of Drosophila, and none in other insects. Conclusions These findings strengthen the hypothesis that nuclear transport gene duplicates in Drosophila evolve either as drivers or suppressors of meiotic drive systems or as other male-specific adaptations circumscribed to flies and involving a handful of nuclear transport functions.